Synthesis and Characterization of Calcium Alginate-Based Microspheres Entrapped with TiO2 Nanoparticles and Cinnamon Essential Oil Targeting Clinical Staphylococcus aureus - Tayyaba Zaineb; Bushra Uzair; Waleed Y. Rizg; Waleed S. Alharbi; Hala M. Alkhalidi; Khaled M. Hosny; Barkat Ali Khan; Asma Bano; Mohammed Alissa; Nazia Jamil (MDPI AG, 2022)
It is important to create new generations of materials that can destroy multidrug-resistant bacterial strains, which are a serious public health concern. This study focused on the biosynthesis of an essential oil entrapped in titanium dioxide (TiO2) calcium alginate-based microspheres. In this research, calcium alginate-based microspheres with entrapped TiO2 nanoparticles and cinnamon essential oil (CI-TiO2-MSs) were synthesized, using an aqueous extract of Nigella sativa seeds for TiO2 nanoparticle preparation, and the ionotropic gelation method for microsphere preparation. The microspheres obtained were spherical, uniformly sized, microporous, and rough surfaced, and they were fully loaded with cinnamon essential oil and TiO2 nanoparticles. The synthesized microspheres were analyzed for antibacterial activity against the clinical multidrug-resistant strain of Staphylococcus aureus. Disc diffusion and flow cytometry analysis revealed strong antibacterial activity by CI-TiO2-MSs. The synthesized CI-TiO2-MSs were characterized by the SEM/EDX, X-ray diffraction, and FTIR techniques. Results showed that the TiO2 nanoparticles were spherical and 99 to 150 nm in size, whereas the CI-TiO2-MSs were spherical and rough surfaced. Apoptosis analysis and SEM micrography revealed that the CI-TiO2-MSs had strong bactericidal activity against S. aureus. The in vitro antibacterial experiments proved that the encapsulated CI-TiO2-MSs had strong potential for use as a prolonged controlled release system against multidrug-resistant clinical S. aureus.